The moderating role of immersion on the motives of watching Mukbang and its consumption: an extended uses and gratifications approach - Chan, Tak Jie; Mat Suhairi, Nur Afiqah; Khairul Ezwan, Nur Hazirah Afiqah; Yang, Tian; Tengku Azzman, Tengku Siti Aisha; Mohd Tajuddin, Syafiqah (Sage Publications, 2025)
The popularity of Mukbang has become a global trend, thus understanding why people watch Mukbang videos can shed light on cultural shifts and consumerism. Therefore, the purpose of this study is to identify the motivation factors that impact Mukbang consumption using the extended Uses and Gratifications (U&G) Theory, with immersion as a moderator. Quantitative research through the online questionnaire was distributed using purposive sampling with 269 valid responses. The results of structural equation modeling revealed that Compensation, Information Seeking, Media Appeal, and Social Presence had a positive and significant impact on Mukbang consumption. However, Enjoyment, Escapism, and Social Interaction were not significantly related. In addition, the moderating role of Immersion was only established between Media Appeal and Mukbang content consumption. The study contributed to the U&G Theory by expanding the new motivation determinants (e.g., Media Appeal, Compensation, Social Presence) and the inclusion of Immersion which is unique in a single framework in emerging markets. The study provided insight to Mukbang content creators and food brand marketers to understand the motivations of the viewers consuming Mukbang content. The findings can help the creators and marketers curate and tailor their content to better engage with the audiences, potentially grow their channels, and improve branding.